Treatment adherence in patients with diabetes mellitus type 2 - Riyan Mulfianda; Nanda Desreza; Khaira Rizki; Rizky Azhari Syam; Rauza Alda; Rizka Dara Vonna (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Diabetes Mellitus (DM) is a chronic disease often referred to as a lifelong disease with chronic complications. The risk of complications of diabetes mellitus can be reduced by effective management of medication therapy by implementing medication adherence. Medication compliance in diabetes mellitus is influenced by various determinants that describe the extent to which the patient's behavior is to comply with taking medication, following a diet, and implementing lifestyle changes per the recommendations recommended by health care providers.Purpose: to analyze the determinants of medication adherence in patients with type 2. Method: The design of this research is quantitative with a cross-sectional study approach. The sample amounted to 97 patients with diabetes mellitus. The statistical analysis used is logistic regression.Results: Showed that the determinants related to medication adherence were age p-value (0.019), education p-value (0.039), Income p-value (0.006), Health Examination p-value (0.034), Blood Sugar Check p-value (0.005), DM knowledge p-value (0.000), and Social Support p-value (0.003), while work p-value (0.136), Length of Suffering from DM p-value (0.399), Use of insulin p-value (0.504), Number of Diseases p-value (0.409), Comorbid p-value (0.583), emotional p-value (0.561) there is no relationship. The most dominant determinant related to medication adherence was the knowledge variable p-value (0.000) with an odds ratio of 0.150 (95% CI: 057-391Conclusion: The most significant determinant of medication adherence is knowledge, so it is recommended to provide continuous and comprehensive updated information about the management of DM, one of which is the diabetes self-management education (DSME) method. The provision of the DSME method can be carried out through a home visit approach to the homes of type 2 DM sufferers.